Above Ground Biomass and Carbon Stock at Pesanggrahan Preserve Area, Malang, East Java, Indonesia - Kundariati, Maisuna; Rohman, Fatchur; Ibrohim, Ibrohim; Nida, Safwatun; Abdul Razak, Sarah; Fardhani, Indra (Universitas Negeri Semarang, 2024)
Tropical forests have known ecosystem services, including sequestering atmospheric carbon and fixing it into biomass. Since the revolutionary industrial changes, the atmospheric carbon level has risen during the recent decades, while the global temperature has increased compared to the pre-industrial levels. Furthermore, reducing atmospheric carbon can mitigate global warming and climate change. This study aims to estimate the aboveground biomass and carbon stock in the Pesanggrahan Forest, Malang Regency, East Java, Indonesia, and contribute local information to the vast global literature. This study was conducted in August 2023 and measured all tree species with a diameter >20 cm in a 5-ha area. The results found 208 individuals and 39 species of trees, the aboveground biomass and carbon stock of which were calculated. The total aboveground biomass (AGB) and carbon stock were 4,486 and 2,248 tons C/ha, respectively. Meanwhile, the total forest AGB and carbon stock in the 5-ha sampling area were 224.77 tons/ha and 112.39 tons C/ha, respectively. These findings highlight the cruciality of tropical forest vegetation in carbon storage and their overall role in regional and global ecosystem management in light of climate change.